Employers and child workers: an institutional approach - Price, R.; Bailey, J.; McDonald, P.; Pini, Barbara (Wiley-Blackwell Publishing Ltd., 2011)
This article explores employers' perspectives on the introduction of child employment legislation in Australia through the lens of the three pillars - regulative, normative and cultural-cognitive - of institutional theory. The study extends the traditional industrial relations (IR) focus on regulation to examine how human resource (HR) practices around child employment become legitimised, normalised and socially supported.